Assessment of significance and relation between risk factors of endometry cancer development in women with endometry hyperproliferative processes - Marichereda, V. G.; Bykova, N. A.; Shevchenko, I. M.; Volyanska, A. G.; Rozhkovskaya, N. M. (Journal of Education, Health and Sport, 2018)
A retrospective analysis of 27 patient case histories with pathomorphologically confirmed diagnosis of endometrial cancer (EC) showed that the most common and statistically significant risk factors for the development of uterine body cancer are: age of a woman above 50 years, heredity and genetic predisposition, late menopause, polycystic ovary syndrome, thyroid gland diseases, diabetes mellitus, obesity, infertility of hormonal genesis, arterial hypertension, inflammatory diseases of female genital organs, early menarche. Hereditary non-polypous colorectal cancer (11.68%, 95% CI 0.59-227.89), and hepatobiliary system diseases (2.50%, 95% CI 0.71-8.72) according to our results are not statistically significant. In order to determine the risk of EC development, 3 rules based on the “AssociationRules method” have been developed. They are: the combination of late menopause and heredity can lead to the development of EC with a probability of 59.25% and accuracy of 88.88%, while the correlation coefficient is 88.88%; the presence of obesity or heredity in a woman above 50 years of age can lead to EC with a probability of 59.25% and accuracy of 80.00% with a correlation coefficient of 84.32%; the development of EC in women above 50 years of age with a late-onset menopause is possible with a probability of 62.96% and accuracy of 94.44%, while correlation coefficient is 89.59% in this case.